The actualization of book museums and regionai culture heritage - Lūžys, Sigitas (Knygotyra, 2003)
One of the most fruitful means of creating the museum is the disclosure of the history of the book as part of the process of culture, which actualizes the cultural heritage, modulates the interpretation of the past. The book must be perceived as a message of certain cultural expression or its product, in the end, as a consistent consequence of the perception of that time.The disclosure of cultural heritage through a book, an integral part of that heritage, demonstrates its historical development and cultural motivation, enhances its acceptance, turning it into our historical property even if it is in other language.The problem of region awareness in Lithuanian cultural self-consciousness also arises. The history of Lithuanian politics, culture and religion discloses exceptional domination of a single center – Vilnius in all political, religious and cultural spheres.The exposition of KRPL book museum covers western Lithuania, which, according to its cultural, political and even religious level is supposed to be an outskirt, and this is the factor enabling us to see and to investigate cultural peculiarities of a remote area.Expositions of provincial museums do not seek to lessen the importance of the central museum, on the other hand, not a single central museum is capable of carrying out the mission for actualization of cultural heritage and, due to the geographical factor, is not able and is not allowed to eliminate the vitality of local museums.The objective of the regional museum is, first, to actualize that layer of culture, which is perceived as its private experience and historical property by the local society. That is why the selection of exhibits must be done considering their informative load, typicality that enables the addressee to accept the provided information of the previous epochs.The museum exhibits must conform the conception of the entire exposition of the museum. The diversity of concepts clashes here. The diversity is determined by the subjective attitude of the creator: his purpose (goals), chosen methods, objective external conditions and, in the end, his perception of the world and the process of history.A concrete book does not appear at any time or from nowhere. The very proveniences of a book exhibit lead to the analysis of cultural phenomena, and the directions of their spread, the situation of the medium and potential consumer, and cultural background in a particular area.The possibilities of a book museum in the process of making cultural heritage of topical issue are rather limited, as old books tend to exclude many national or cultural spheres. Through the addressee of a book were vast masses of working people in very rare cases; in fact, the old book was the form of cultural expression of the elite mainly. Therefore, it is not by accident that book museums are oriented into the church, manor or town culture in which the most intensive roads of book migration meet and the main creators and consumers find their place.In almost all the manor, church, school and town culture in the Grand Duchy of Lithuania is represented in other than the Lithuanian language. The book related to this culture is also in other than the Lithuanian language. The culture of the country being represented through the book faces the problem of property: how much the cultural phenomena, experience or means of their realization is the historical property of the country and how much of it is the manifestation of a foreign culture which had no influence on the local culture.
Keywords: -